Analysis of Blocking Skills of Bolavoli Players at Smp Negeri 7 Bermani Ilir Extracurricular Students - Putra, Satria Adi; Martiani, Martiani; Sumantri, Ajis (Universitas Dehasen Bengkulu, 2024)
The purpose of this study was to discuss research to determine the Blocking Ability of Bolavoli Players of students at SMP Negeri 7 Bermani Ilir. The research method used is a survey using tests. The population was 20 male students and the sample in this study used purposive sampling, namely all students at SMP Negeri 7 Bermani Ilir as many as 20 students. The data collection method used in this study was a measurement test. The data analysis technique used is descriptive percentage statistics. The results for the